Lessons Learned from OpenNotes Learning Mode and Subsequent Implementation across a Pediatric Health System - Murugan, Avinash; Gooding, Holly; Greenbaum, Jordan; Boudreaux, Jeanne; Blanco, Reena; Swerlick, Arin; Sauer, Cary; Liu, Steven; Bhatia, Amina; Carter, Alexis; Burris, Meredith M.; Becker, Lauren; Abney, Lashandra; O'Brien, Sharon; Webb, Shane; Popkin, Melissa; Williams, Herb; Jennings, Desiree; Orenstein, Evan W. (Applied Clinical Informatics, 2022)
Background The 21st Century Cures Act has accelerated adoption of OpenNotes, providing new opportunities for patient and family engagement in their care. However, these regulations present new challenges, particularly for pediatric health systems aiming to improve information sharing while minimizing risks associated with adolescent confidentiality and safety.Objective Describe lessons learned preparing for OpenNotes across a pediatric health system during a 4-month trial period (referred to as “Learning Mode”) in which clinical notes were not shared by default but decision support was present describing the upcoming change and physicians could request feedback on complex cases from a multidisciplinary team.Methods During Learning Mode (December 3, 2020–March 9, 2021), implementation included (1) educational text at the top of commonly used note types indicating that notes would soon be shared and providing guidance, (2) a new confidential note type, and (3) a mechanism for physicians to elicit feedback from a multidisciplinary OpenNotes working group for complex cases with questions related to OpenNotes. The working group reviewed lessons learned from this period, as well as implementation of OpenNotes from March 10, 2021 to June 30, 2021.Results During Learning Mode, 779 confidential notes were written across the system. The working group provided feedback on 14 complex cases and also reviewed 7 randomly selected confidential notes. The proportion of physician notes shared with patients increased from 1.3% to 88.4% after default sharing of notes to the patient portal. Key lessons learned included (1) sensitive information was often present in autopopulated elements, differential diagnoses, and supervising physician note attestations; and (2) incorrect reasons were often selected by clinicians for withholding notes but this accuracy improved with new designs.Conclusion While OpenNotes provides an unprecedented opportunity to engage pediatric patients and their families, targeted education and electronic health record designs are needed to mitigate potential harms of inappropriate disclosures.
Keywords: electronic health records and systems; patient portal; confidentiality; 21st Century Cures Act; OpenNotes